Effects of Arm Swing on Plantar Pressure Behavior During Walking - Leblebici, Gökçe; AKALAN, NAZİF EKİN; ÖNERGE, KÜBRA; KUCHIMOV, SHAVKAT; Ören, Meryem (İstanbul Üniversitesi-Cerrahpaşa Sağlık Bilimleri Fakültesi, 2023)
Objective: This study aimed to investigate the influence of different arm swing conditions on plantar pressure behavior during walking in healthy individuals. Methods: The study included 29 healthy (22.55 ± 1.02 years) volunteers. The foot pressure was analyzed under 3 conditions: both arms should be freely swinging and the dominant arm should be restricted and should be held. Time and magnitudes of peak forces, gait velocity, duration of stance subphases, peak forces for 5 different areas in foot-sole, accelerations of the center of pressure, and mediolateral displacements of center of pressure were the interesting parameters. Results: When the arm swing was held, the onset of terminal stance was earlier and the anterior-posterior center of pressure acceleration decreased at the midfoot on the affected side (0.32 ± 0.04 seconds, 2.96 ± 0.27 m/ms 2) than on the contralateral side (0.34 ± 0.05 seconds, 3.12 ± 0.28 m/ms 2) (P = .04, P = .02). The differ- ences in anterior-posterior center of pressure acceleration between heel and forefoot and the mediolateral displacements of center of pressure were lower on the affected side at held (3.75 ± 0.31 m/ms 2, 0.06 ± 0.02 m, respectively) compared to the free swing (3.82 ± 0.30 m/ms 2, 0.07 ± 0.02 m) (P = .02, P = .01), while the peak force at the medial forefoot was lower on the contralateral side when the arm was held (28.87 ± 6.22 N) compared to the free swing (30.54 ± 5.86 N) (P= .01). Conclusion: The lack of arm swing may interact with ipsilateral early onset and longer late stance phase during walking in healthy individuals. The foot pressure behaviors during walking should be investigated for unilaterally affected patients.
Keywords: Arm Swing; Foot Pressure; Gait